2006
DOI: 10.1177/0165551506059226
|View full text |Cite
|
Sign up to set email alerts
|

A connectionist and multivariate approach to science maps: the SOM, clustering and MDS applied to library and information science research

Abstract: Abstract.The visualization of scientific field structures is a classic of scientometric studies. This paper presents a domain analysis of the library and information science discipline based on author co-citation analysis (ACA) and journal cocitation analysis (JCA). The techniques used for map construction are the self-organizing map (SOM) neural algorithm, Ward's clustering method and multidimensional scaling (MDS). The results of this study are compared with similar research developed by Howard White and Kat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 27 publications
4
38
0
2
Order By: Relevance
“…3D MDS maps (authors' approach) and SOM have shown the better properties than VOS and VxOrd. These results have proved the findings and interpretations obtained from qualitative analysis [9]. Given maps have revealed essential changes in computer science literature during the time of the development of the CCS classification compared.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…3D MDS maps (authors' approach) and SOM have shown the better properties than VOS and VxOrd. These results have proved the findings and interpretations obtained from qualitative analysis [9]. Given maps have revealed essential changes in computer science literature during the time of the development of the CCS classification compared.…”
Section: Discussionsupporting
confidence: 74%
“…1 Interface screenshot -the prototype of application for semantic browsing researchers concluded that maps constructed using VOS approach provide a more satisfactory representation of the underlying dataset [8]. MDS-VOS tests revealed the first one is distance preserving while the second -topology preserving technique [9], [10].…”
Section: Iimapping Previewmentioning
confidence: 99%
“…Identifying an equal number of male and female coevals was not easy. We found that "most-cited" lists of information science researchers (e.g., Moya-Anegon, Herrero-Solana, & Jimenez-Contreras, 2006;White, 2003) Table 1.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Pioneering work on grouping of journals into subject categories based on reference/citation analysis was carried out by PINSKY & NARIN [1976]. An alternative way to group journals is journal co-citation analysis, based on the number of times any pair of journals is cited in the same source article (e.g., [MOYA-ANEGON & AL., 2006].…”
Section: Introductionmentioning
confidence: 99%